The Relationship Between Ultra-Processed Food Consumption And Obesity In Adolescent: A Narrative Review - Aisy Laili Rahma (International Journal of Health Engineering and Technology, 2026)
The rising global prevalence of obesity is a public health issue, with dietary factors increasingly recognized as root to its development. Ultra-processed foods (UPFs), a common modern diet, are characterized by high industrial processing with high energy density but poor in essential nutrients. This literature review aims to synthesize current evidence regarding the relationship between the consumption of UPFs and the incidence of obesity in adolescents. It investigates the consistency of this association, underlying mechanisms, and variations across populations. A systematic search was conducted using relevant keywords and search terms related to ultra-processed foods, food processing, obesity, weight gain, body mass index, and adolescents. Epidemiological studies employing diverse methodologies, including cohort and cross- sectional designs, consistently suggest a positive association between higher UPF intake and increased risk of overweight and obesity in adults and children. Potential mechanisms underlying this association are the energy density and palatability of UPFs, their impact on appetite and satiety, and their substitution for more nutrient-dense with minimal process. Strong evidence suggests UPF consumption is a significant risk factor for obesity development. Public health strategies should prioritize reducing ultra- processed food consumption via labeling, guidelines, and promotion of minimally processed foods, while further research strengthens causal inference and effective interventions.